Prevalence of Postoperative Anemia among Adult Surgical Patients at Comprehensive Specialized Hospital. - Tegegne, Shimelis Seid; Alle, Yewlsew Fentie; Lemma, Diriba Teshome; Aytolign, Habtu Adane (Indian Journal of Surgery, 2025)
Postoperative anemia has been observed to increase the risk of oxygen deprivation, postoperative morbidity, and mortality. However; the prevalence of postoperative anemia prevalence in Ethiopia remains poorly understood. Reports from various literatures regarding postoperative anemia prevalence aboard are also inconsistent. This study aimed to determine the prevalence of postoperative anemia and associated factors among post-surgical patients. A hospital-based cross-sectional study was conducted involving 409 post-surgical patients. Data were collected using an interviewer-administered semi-structured questionnaire. Bivariable and multivariable analyses were performed using the Statistical Package for Social Science 23.0 program to determine the association between the independent variables and the surgical outcomes. The hemoglobin test result revealed that 203 (49.6%) of the participants were anemic at the time of hospital discharge. The study found that patients older than 50 years, unemployed, those with preoperative anemia, an American Society of Anesthesiologist physical status score of IV, emergency surgery, intraoperative blood loss greater than 500 ml, and hospital stay longer than 2 weeks were at significantly increased risk for postoperative anemia. The prevalence of postoperative anemia was high. Clinicians must be aware of the risk factors associated with postoperative anemia to minimize complications and improve patients' perioperative quality of life.